Test of the External-Casing Optical Fiber Intelligent Completion Technology for Horizontal Wells in Bottom-Water Reservoirs - Li Dajian; Wu Chunsheng; Cui Ziyue; Wang Xu; Yang Haitao; Gao Yu (Shiyou jixie)
In the production process of horizontal wells in bottom-water reservoirs， water production and flooding caused by bottom-water coning are key factors restricting the development effect of horizontal wells. There is an urgent need to figure out effective techniques of water control in the whole life cycle of bottom-water reservoirs. In Changqing Oilfield， water production and flooding occur in horizontal wells for developing bottom-water reservoirs. To solve these problems， for purpose of the integration of performance monitoring and control at producing intervals， following the idea of intelligent completion of oil wells， and combining with the conditions of well completions， a solution of water control during intelligent completion was proposed， which incorporates the external-casing distributed optical fiber for permanent monitoring on production performance at the producing interval and the switchable sliding sleeve of casing for performance control at the producing interval. A string consisting of external-casing distributed optical fiber + switchable sliding sleeve of casing + permanent downhole gauge was designed innovatively， and supporting key tools were designed and manufactured. Thus， a new intelligent completion technology for horizontal wells in bottom-water reservoirs was formed， and it has been tested at Well Chi97H*. The results show that the use of the external-casing distributed optical fiber for continuous， real-time monitoring and interpretation of the temperature， acoustic vibration and downhole pressure signals of the whole wellbore， especially the producing interval， helps fully understand the performance at the producing interval and locate the water-producing interval， so that the sliding sleeve of casing at the corresponding interval is closed to resume the well productivity. In this way， the water-flooded wells in bottom-water reservoirs can be effectively controlled. The study demonstrates that the external-casing optical fiber intelligent completion technology for horizontal wells is an effective option to realize the water control in bottom-water reservoirs.